Berdakwah dalam Konteks Kebebasan Beragama - Asmaya, Enung (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2008)
Religiosity is basic need of human beings. It is needed to guide human beings in achieving their happiness in life. If human beings hove realized that they con rely on their religious belief, none can force them to embrace a new Â religion. Da'wo odivity, in relation to religious freedom, must not be done through an unethical force to make someone convert his religious belief. It should offer on Â open dialogue to search for the truth. Religiousity is one's belief in a religion, deep in his heart, which can drive him to purify his religion from weakness. There is no one who has the right to ;ustify that the religion he embraces is wrong. If such case happens, this means that human right for religious belief hos been disrespeded.